Multi-Task Simultaneous Supervision: Dual Resource-Constrained Scheduling Problem in Identical Parallel Machines Considering Differences in Operator Skill Levels - Rizka, Afifah; Sukoyo, Sukoyo; Akbar, Muhammad (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2024)
This paper focuses on developing a Multi-Task Simultaneous Supervision Dual Resource-Constrained Scheduling (MTSSDRC) system that considers differences in skill between operators, aiming to minimize makespan and balance operator workload. Workload balance is calculated using the Workload Smoothness Index (WSI). The mathematical model developed uses three techniques: Mixed-Integer Linear Programming (MILP), Mixed-Integer Quadratic Programming (MIQP), and Mixed-Integer Quadratically Constrained Programming (MIQCP). These techniques can handle scheduling cases on a small to medium scale. Results from MILP focus on minimizing makespan, with an additional constraint for calculating the WSI. MIQP focuses on workload balance so that the WSI value becomes an objective function. It also adds a constraint for the allowable makespan value. The result from MIQP shows that the WSI value is lower than in MILP, and the makespan values are equal to the MILP makespan value. Next, MIQCP aims to minimize makespan with a constraint for the allowable WSI value. The MIQCP model produces a makespan value adjusted to a WSI value close to zero. Finally, further analysis is presented regarding the influence of differences in operator skills based on the results of the three models. Based on these models, operators with better skills will be assigned more frequently than others.